Diurnal variation of stomatal resistance to water vapor diffusion in irrigated peanuts - Carlos Silva, Luiz; Fideles Filho, José; Esberard de Macêdo Beltrão, Napoleão; Venkata Ramana Rao, Tantravahi (Pesquisa Agropecuaria Brasileira, 1998)
The plant response of the peanut (Arachis hypogaea L.) crop submitted to two different levels of irrigation was evaluated with the objective of determining the diurnal variation of the stomatal resistence of the BR-1 cultivar, and was related with the photon flux density of the photosynthetically active radiation. The experiment was conducted at the Experimental Station belonging to the Companhia de Desenvolvimento do Vale do São Francisco, situated in the municipality of Rodelas, BA, Brazil. The soil is classified as fine sandy soil. The experiment was conducted during the period of August to December 1994. The planting took place on the 6th of August, 1994. The amounts of irrigation applied were 300 mm and 700 mm, and the irrigations were applied at four-day intervals. The leaf stomatal resistences and the photon flux density of the photosynthetically active radiation were measured. Under non-stressed conditions, the peanut crop shows a hyperbolic relation between the stomatal resistence and photon flux density. The water stressed plants present the phenomenon of stomatal closure around midday.